A Initiation of Disaster Prepared School at Cinjur Development Agricultural Vocational High School - Situmorang, Marningot Tua Natalis; Linda Noviana (LPPM Institut Studi Islam Sunan Doe, 2024)
In order for students to understand disasters properly and completely, disaster education in schools must be integrated into several subjects. The Cianjur Development Agricultural Vocational Middle School is a school located in the Cibeber area, Cilaku Regency. Cianjur, with a total of 561 students (293 male students and 268 female students). As an educational institution, the Cianjur Development Agricultural Vocational School is responsible for organizing education so that students can develop their potential and build a culture, including a disaster preparedness culture. According to the Cianjur Regency Regional Disaster Risk Map, Cibeber is very vulnerable to the risk of hurricanes, floods and earthquakes. The knowledge of educators on disaster management regarding attitudes/actions, school policies, preparedness planning, and resource mobilization still needs to be improved. This partner problem can be overcome through assistance and training at disaster preparedness schools or disaster education units. The implementation team and relevant experts provide support and training. In this early stage of community service, preparedness training will be carried out for class VII students, and will describe the initial knowledge of school residents on disaster preparedness by conducting a survey. An ongoing program to prepare disaster preparedness schools needs to be carried out.